Associated Factors of Quality of Life in Adult Female Acne Coexisting with Hyperandrogenism and Polycystic Ovarian Syndrome using the Dermatology Life Quality Index - Jirawattanadon P. (2023)
Objective: This study aimed to assess the effects of AFA and its associated factors, especially those coexisting with hyperandrogenism or PCOS, on QoL using the Dermatology Life Quality Index (DLQI). Materials and Methods: A retrospective cross-sectional study was conducted on AFA patients who had been treated between May 2018 and January 2020. Dermatologists had performed history taking and determined the clinical severity of the acne, and gynecologists had identified PCOS. Aggravating factors and DLQI were self-reported by the patients. Results: A total of 208 AFA patients, aged 31.8±7.1 years on average, were included. The mean DLQI score was 8.0±5.4 (range: 0-23). Patients with moderate to severe acne had significantly higher total DLQI scores compared to those with almost clear to mild acne (P=0.043). Similarly, patients who reported acne aggravated by diet, androgenetic alopecia, or perioral and chin lesions had significantly higher total DLQI scores (P=0.025, P=0.049, and P=0.014, respectively). However, PCOS and hirsutism did not significantly impact QoL. The aspect most affected was feeling embarrassed and self-conscious, with significantly greater impacts observed in patients with moderate to severe acne compared to mild acne. The daily activities of patients with androgenetic alopecia were significantly impacted in terms of their choice of clothes and sexual difficulties. Conclusion: AFA mostly had a moderate to extremely large effect on patients’ QoL. Knowing the factors influencing QoL, such as acne severity, dietary aggravation of acne, and androgenetic alopecia, may enable physicians to improve the QoL of patients.